2007
DOI: 10.1002/app.26326
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinked poly(octadecene‐alt‐maleic anhydride) copolymers as crude oil sorbers

Abstract: Crosslinked octadecene (OD) and maleic anhydride (MA) copolymer MA/OD (50 : 50 mol ratios) was prepared by condensation of the prepared linear copolymer with different glycols. Ethylene glycol and polyethylene glycols having different molecular weights were used as crosslinking agents. The crosslinked copolymers were evaluated for oil-absorbency application. The effect of glycol type, composition; crosslinker wt % and type of oil on swelling properties of crosslinked polymers were studied through the oil absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 28 publications
0
32
0
1
Order By: Relevance
“…For some oil-absorbents in literature, soluble fraction (SF) (Atta et al, , 2006(Atta et al, , 2007a(Atta et al, , 2007b or gel fraction (GF) (Zhou & Cho, 2002) was measured to investigate the cross-linking of the absorbent networks. In the present study, cross-link degree (D) of the oil-absorbents was determined in a similar way to characterize the oil-absorbents.…”
Section: Cross-link Degreementioning
confidence: 99%
See 2 more Smart Citations
“…For some oil-absorbents in literature, soluble fraction (SF) (Atta et al, , 2006(Atta et al, , 2007a(Atta et al, , 2007b or gel fraction (GF) (Zhou & Cho, 2002) was measured to investigate the cross-linking of the absorbent networks. In the present study, cross-link degree (D) of the oil-absorbents was determined in a similar way to characterize the oil-absorbents.…”
Section: Cross-link Degreementioning
confidence: 99%
“…Oil absorption test 2.6.1. Oil absorbency The oil absorbency (Q) was determined by the method reported in literature (Atta et al, , 2006(Atta et al, , 2007a(Atta et al, , 2007bKulawardana & Neckers, 2010;Wu & Zhou, 2009b;Zhou & Cho, 2001. A quantity of about 0.02 g of dried oil-absorbent sample with known weight (m 3 ) was put into a filter bag and immersed in four different oils (tetrachloromethane, chloroform, xylene, and toluene) at room temperature.…”
Section: Cross-link Degreementioning
confidence: 99%
See 1 more Smart Citation
“…The presence of two absorption peaks at 1810 and 1770 cm −1 , assigned for the carbonyl of the anhydride group, confirms the presence of MA in the structure of the produced copolymers. The appearance of these bands indicates that the anhydride groups were not hydrolyzed during the copolymerization of AA with MA [19]. It was also observed that, the absorption bands at 3100 and 1600 cm −1 , assigned to =CH and C=C, disappeared in all spectra of MA/AA copolymers and confirm the complete polymerization of AA and MA monomers.…”
Section: Copolymerization Of Ma/aamentioning
confidence: 75%
“…Сшитые сополимеры МА/ ТД и МА/ОК (50:50 моль/моль) получали кон-денсацией линейных сополимеров с различными гликолями. Те же авторы [34] получили сшитый сополимер октадецена (ОД) и малеинового анги-дрида МА/ОД (50:50 моль/моль) конденсацией соответствующего линейного сополимера с различными гликолями (в качестве сшивающих агентов использовали этиленгликоль и полиэти-ленгликоли с разной молекулярной массой). Изу-чали влияние типа гликоля, состава, содержания сшивающего агента и типа нефти на набухание в ней сшитых сополимеров.…”
Section: другие нефтесорбентыunclassified